Impact of a standardised rapid response system on clinical outcomes of female patients: an interrupted time series approach. Issue 3 (4th August 2022) - Chen, Jack; Ou, Lixin; Hillman, Ken; Parr, Michael; Flabouris, Arthas; Green, Malcolm
Abstract : Background: This study aimed to assess the impact of a standardised rapid response systems (the Between the Flags (BTF)) implemented across New South Wales (NSW), Australia, among female patients. Methods: We conducted an interrupted time series (2007–2013) population-based linkage study including 5 114 170 female patient (≥18 years old) admissions in all 232 public hospitals in NSW. We studied changes in levels and trends of patient outcomes after BTF implementation among four age groups of female patients. Results: Before the BTF system introduction (2007–2009), for the female patients as a whole, there was a progressive decrease in rates of in-hospital cardiopulmonary arrest (IHCA), IHCA-related mortality and hospital mortality for female patients. However, there were no changes in deaths in low-mortality diagnostic-related groups (DLMDRGs), IHCA survival to discharge and 1-year post-discharge mortality after surviving an IHCA. Only the female patients aged 55 years and older showed the same results as the whole sample. After the BTF programme (2010–2013), the same trends (except for DLMDRG) continued for female patients as a whole and for those aged 55 years or older. There was a significant reduction in DLMDRG among female patients aged 35–54 years (p<0.001), those aged 75 years and over (p<0.05) and female patients as a whole (p<0.05). The decreasing secular trend of surviving an IHCA to hospital discharge before the BTF system (p<0.05) among patients aged 18–34 years old was reversed after the BTF implementation (p<0.01). Conclusions: For female patients the BTF programme introduction was associated with continued reductions in the rates of IHCA, IHCA-related mortality and hospital mortality, as well as a new reduction in DLMDRG for 35–54 years old patients and those aged 75 years and older, and increased survival for those aged 18–34 years who had suffered an IHCA.